BIOLOGICAL SCIENCE IN THE GENERAL EDUCATION PROGRAM AT IOWA STATE TEACHERS COLLEGE. - Winier, Leonard Philip (Science Education, 1954)
The article focuses on biological science in the general education program at Iowa State Teachers College in Iowa. The study aimed: (1) to establish a philosophy of science education compatible with the goals of general education: (2) to survey the professional literature dealing with general education and the role of science; (3) to study the curricular programs of colleges that have made outstanding contributions in the field; (4) to consider general education in terms of student interests and needs; and (5) to give careful attention to the views of the staff members at the college engaged in assisting in the planning of the course. The author points out that social attitudes play a significant role in general education. Furthermore, extending the limits of the subject matter in the field of biology in order to achieve some degree of success is necessity in developing the course in biological sciences for the general education program.